A review of the Miocene record of Pampatheriidae (Mammalia, Xenarthra) from Uruguay - Bostelmann, Enrique (2010)
The Pampatheriidae represents an extinct group of cingulates whose remains are mostly known from Quaternary sediments. Contrary, the Mio-Pliocene record of the group is infrequent and largely based on fragmentary materials. In Uruguay, Miocene Pampatheriidae has been described almost exclusively on the basis of isolated osteoderms assigned to Kraglievichia paranense (Ameghino). A few communications also refer to the possible occurrence of the genus Vassallia Castellanos. In this contribution we review the taxonomic status of those past mentions and present three sets of unpublished materials deposited in the collections of the Museo Nacional de Historia Natural (MNHN), and the Paleontological Museum of the Real de San Carlos (AC). MNHN 2528 includes two fixed osteoderms associated with a nearly complete skull preserving the full dental series except for both M1 and the right M2, and the apex of the rostrum (part of the premaxilla and the nasal regions). MNHN 1482 includes numerous osteoderms, partially complete mandibular rami, the right ulna, the left astragalus and a fragment of the pelvis, all belonging to one specimen. Both fossils were exhumed from the Balneario Arazatí (San José Department) in sediments of the Camacho Formation (late Miocene, Huayquerian SALMA), and are provisionally assigned to Vassallia sp. AC 1050 is an almost completely articulated carapace which contains part of the skull, several isolated osteoderms and some vertebrae, collected in the marine facies of the San Pedro Member of the Camacho Formation, in Colonia Department. This material has a particular set of morphological features (i.e., configuration of the teeth, patterns of ornamentation in the osteoderms) which demands to be cautious on its taxonomical allocation. The finding of these associated cranial and exoskeletal remains becomes an important element for the current review of the taxonomy of the Mio-Pliocene South American Pampatheriidae.